Analysis of the Role of the Special Job Exchange (BKK) on Increasing the Absorption of Alumni of the State Vocational School of Palembang City in the World of Work - Mondyaboni Mondyaboni; Nur Ahyani; Syaiful Eddy (International Journal of Educational Technology and Society, 2025)
This research aims to analyze the role of the Special Job Exchange (BKK) in increasing the absorption of Palembang City State Vocational School alumni in the world of work. BKK is one of the units that supports the labor absorption process by connecting the world of education and the world of industry. This research uses a qualitative approach with a case study method involving primary data through in-depth interviews with BKK, alumni and collaborating companies. The research results show that BKK has a significant role in facilitating Palembang City State Vocational School alumni in obtaining employment opportunities. Apart from that, BKK also provides training and information regarding job vacancies that are relevant to the skills possessed by alumni. However, several challenges are still faced, such as a lack of certain skills needed by companies and limited collaboration networks with the industrial world. This research recommends the need to improve the quality of training and expand the cooperation network between vocational schools and the industrial world to increase the effectiveness of BKK in accelerating workforce absorption.